Functional processed cheese: development of new technology - Gumarova, А.; Baybatyrov, T.; Japarova, A. (The journal of Almaty Tehnologial University, 2019)
The article presents data on the use of a dry mixture of rose hips, cranberries and turmeric for the production of processed cheese for functional purposes. The inclusion 2%, 3%, 5% of vitamin herbal supplements, increases storage capacity, improves organoleptic, physico-chemical parameters and nutritional value of processed cheese and does not require changes in the process. В статье рассматриваются результаты исследований технологии производства плавленного сыра функционального назначения с добавлением смеси шиповника, клюквы и куркумы. Включение 2%, 3% и 5% витаминной растительной добавки, увеличивает хранимоспособность, улучшает органолептические, физико-химические показатели и пищевую ценность плавленного сыра и не требует изменений технологического процесса.
Keywords: рк; food industry; отечественное издание; научный журнал; периодическое издание; журнал коксон; recipe; processed cheese; vitamins; herbal supplements; cranberries; rose hips; turmeric; рецептура; плавленный сыр; витамины; растительные добавки; клюква; шиповник; құрқұма